Validation and implementation of group electronic hand hygiene monitoring across twenty-four critical care units. (25th July 2022) - Leis, Jerome A.; Obaidallah, Maryam; Williams, Victoria; Muller, Matthew P; Powis, Jeff E.; Johnstone, Jennie; Hota, Susy; Katz, Kevin; Payne, Michael; Castellani, Lucas; Downing, Mark; Mertz, Dominik; et al.
Abstract: Objectives: An accurate estimate of the average number of hand hygiene opportunities per patient hour (HHO rate) is required to implement group electronic hand hygiene monitoring systems (GEHHMSs). We sought to identify predictors of HHOs to validate and implement a GEHHMS across a network of critical care units. Design: Multicenter, observational study (10 hospitals) followed by quality improvement intervention involving 24 critical care units across 12 hospitals in Ontario, Canada. Methods: Critical care patient beds were randomized to receive 1 hour of continuous direct observation to determine the HHO rate. A Poisson regression model determined unit-level predictors of HHOs. Estimates of average HHO rates across different types of critical care units were derived and used to implement and evaluate use of GEHHMS. Results: During 2, 812 hours of observation, we identified 25, 417 HHOs. There was significant variability in HHO rate across critical care units. Time of day, day of the week, unit acuity, patient acuity, patient population and use of transmission-based precautions were significantly associated with HHO rate. Using unit-specific estimates of average HHO rate, aggregate HH adherence was 30.0% (1, 084, 329 of 3, 614, 908) at baseline with GEHHMS and improved to 38.5% (740, 660 of 1, 921, 656) within 2 months of continuous feedback to units ( P < .0001). Conclusions: Unit-specific estimates based on known predictors of HHO rate enabled broad implementation of GEHHMS. Further longitudinal quality improvement efforts using this system are required to assess the impact of GEHHMS on both HH adherence and clinical outcomes within critically ill patient populations.